(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The paper deals with the implicit meanings of Matsuo Bashō’s haiku from the perspective of Zen Buddhism philosophy. Particularly, the peculiarity of Zen Buddhism has been determined, the specific of Zen Buddhism motives in Matsuo Bashō’s haiku has been studied, and the poet’s works have been analyzed from the perspective of Zen Buddhism.